The role of forkhead box 1 (FOXO1) in the immune system: Dendritic cells, T cells, B cells, and hematopoietic stem cells - Cabrera-Ortega, Adriana Alicia [UNESP]; Feinberg, Daniel; Liang, Youde; Rossa, Carlos [UNESP]; Graves, Dana T. (Begell House, 2017)
Forkhead box-O (FOXO) transcription factors have a fundamental role in the development and differentiation of immune cells. FOXO1 and FOXO3 are FOXO members that are structurally similar and bind to the same conserved consensus DNA sequences to induce transcription. FOXO1 has been studied in detail in the activation of dendritic cells (DCs), where it plays an important role through the regulation of target genes such as ICAM-1, CCR7, and the integrin αvβ3. FOXO1 is activated by bacteria challenge in DCs and promotes DC bacterial phagocytosis, migration, homing to lymph nodes, DC stimulation of CD4+ T cells and resting B cells, and antibody production. Deletion of FOXO1 in DCs enhances susceptibility to bacteria-induced periodontal disease. FOXO1 and FOXO3 maintain naive T cell quiescence and survival. FOXO1 and FOXO3 enhance the formation of regulatory T cells and inhibit the formation of T-helper 1 (Th1) and Th17 cells. FOXO1promotes differentiation, proliferation, survival, immunoglobulin gene rearrangement, and class switching in B cells, but FOXO3 has little effect. Both FOXO1 and FOXO3 are important in the maintenance of hematopoietic stem cells by protecting them from oxidative stress. This review examines FOXO1/FOXO3 in the adaptive immune response, key target genes, and FOXO inhibition by the phosphoinositide 3-kinase/AKT pathway.
Keywords: Acquired immunity; Antibody; Forkhead; Inflammation; Lymphocyte; Protein kinase B (AKT)